Comparative study of fracture shaft humerus treated by dynamic compression plate and interlocking nailing - Dr. Anand Kumar Goyal, Dr. Girish Dang, Dr. Vikrant Sharma (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Commonly deployed surgical procedures for humerus shaft fracturesinclude dynamic compression plating and interlocking nailing. This study compareddynamic compression plating (Group A) and interlocking nailing (Group B) in a cohort of 100 patients.